3.0k views
2 votes
Which of ghe following is equivalent to (x+4)(3x^2+2x)?

User Hugh Hou
by
5.9k points

1 Answer

3 votes

The given expression is


(x+4)(3x^2 +2x)

And in the second factor, x is common. So on taking x out, we will get


(x+4)(x)(3x+2) = x(x+4)(3x+2)

We can expand it by distributing , that is


(x+4)(3x^2 +2x) = x(3x^2 +2x) +4 (3x^2 +2x)


= 3x^3 +2x^2 + 12x^2 +8x

Combining like terms,


= 3x^3 +14x^2 +8x

And that's the expanded form ., and the given expression can also be written in that way .

User Jeffrey Harris
by
5.3k points